TUMORES DE LA GLANDULA PINEAL ALGUNOS DATOS SOBRE LA ESTRUCTURA HISTOLOGICA DE LOS PINEALOMAS - ALVAREZ FUERTES, G (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1948)
Various types of lighting are discussed and illumination is recommended as follows: Belling for teaching; Critical for clinical work and Kohler for research
AN ESC NAC CIENC BIOL
Keywords: TUMORES, GLANDULA PINEAL, DATOS, ESTRUCTURA HISTOLOGICA, PINEALOMAS; CIENCIAS DE LA VIDA; BIOLOGIA HUMANA; FISIOLOGIA HUMANA